Ethnobiology and Shifting Baselines: An Example Reinterpreting the British Isles’ Most Detailed Account of a Sea Serpent Sighting as Early Evidence for Pre-Plastic Entanglement of Basking Sharks - France, Robert (Ethnobiology and Conservation, 2019)
Abstract Recognizing shifts in baseline conditions is necessary for understanding long-term changes in populations as a prelude to implementing present-day management actions and setting future restoration goals for anthropogenically-altered marine ecosystems. Examining historical information contained within anecdotal accounts from non-traditional sources has previously proven useful in this regard. Herein, I scrutinize eyewitness descriptions and illustrations related to the most detailed nineteenth-century report of sighting a purported sea serpent in the British Isles. I then reinterpret this anecdote (as well as complementary evidence offered by cryptozooloogists in its support obtained from other sightings of similarly described unidentified marine objects), suggesting it to provide one of the earliest descriptions of the non-lethal entanglement of an animal—in this case what I believe to have been a basking shark—in European waters. The present work suggests that the entanglement of sharks in fishing gear or hunting equipment has a much longer environmental history than is commonly believed, and provides another example of how ethnozoological studies can contribute toward recognizing past fishing-related pressures and baseline shifts in affected populations. Sharks, it seems, have been subjected to the impacts of not just direct fishery exploitation but also through becoming by-catch, long before the advent and widespread use of plastic in the middle of the twentieth century.